2007
DOI: 10.1080/07357900701359577
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Augments Gemcitabine Cytotoxic Effect on Pancreatic Adenocarcinoma Cell Lines

Abstract: The increased cytotoxic effect of the combination on cell survival and on the induction of apoptosis in COX-2 expressing pancreatic cancer cells is probably associated with downregulation of COX-2 and p-ERK1/2 levels. This finding may contribute to the development of an effective treatment of pancreatic adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(58 citation statements)
references
References 38 publications
1
53
0
2
Order By: Relevance
“…Studies have shown co-treatments of curcumin and gemcitabine [37], beta-phenylethyl isothiocyanate [38], epigallocatechin gallate [39], and taxol [40] were synergistically cytotoxic to cancer cells. We attempted to examine whether the combinations of curcumin and DNICs also had a synergistic cytotoxic effect against melanoma cells.…”
Section: Cytotoxicity Of Dnics Combined With Curcuminmentioning
confidence: 98%
“…Studies have shown co-treatments of curcumin and gemcitabine [37], beta-phenylethyl isothiocyanate [38], epigallocatechin gallate [39], and taxol [40] were synergistically cytotoxic to cancer cells. We attempted to examine whether the combinations of curcumin and DNICs also had a synergistic cytotoxic effect against melanoma cells.…”
Section: Cytotoxicity Of Dnics Combined With Curcuminmentioning
confidence: 98%
“…In particular, CUR has demonstrated a potent ability to increase the efficacy of conventional cancer therapies and to chemosensitize cells of colorectal, HNSCC, pancreatic, bladder, and breast tumors [122,123,124,125,126,127,128,129,130]. Shakibadei et al demonstrated that CUR increased the effect of 5-fluorouracil (5-FU) against the colorectal cancer cell lines HCT116 and HCT116+ch3 (complemented with chromosome 3).…”
Section: Combinations Of Polyphenols and Anticancer Drugs: In Vitrmentioning
confidence: 99%
“…The enhanced growth inhibition has been found to be associated with significant down-regulation of COX-2 expression under the combination treatment condition. Curcumin also increased the inhibitory effect of gemcitabine on pancreatic cancer cell proliferation, and potentiated pro-apoptotic activity of gemcitabine through the down-regulation of COX-2 and p-ERK1/2 (53). In addition, curcumin analog CDF with higher bioavailability has been synthesized and the effect of CDF on COX-2 expression and pancreatic cancer growth have been tested.…”
Section: Nutraceuticals For Pancreatic Cancer Treatmentmentioning
confidence: 99%